Precipitation : earth surface responses and processes - Rodrigo-Comino, Jesus (Elsevier, 2021)
Precipitation is a key factor needed for understanding landscape evolution and ecosystem services. Knowing the main precipitation composition, mechanisms and processes allows for efficient land management plans and ecosystem restoration activities. However, precipitation shows different responses under specific environments depending on the climate (from the arid to the polar areas), parent material, scale (from the raindrops to catchment scale), intensity, landscape morphologies (soil sealing, rills, gullies or rivers) or human activities (agriculture or urban areas). Precipitation: Earth Surface Responses and Processes bring this information together and provides indispensable material in a holistic manner for students, scientists and lecturers from different environmental disciplines such as climatology, meteorology, geomorphology, hydrology, soil science, geography, engineering, or ecology.--